High on-treatment platelet reactivity and P2Y12 antagonists in clinical trials - Trenk, Dietmar; Kristensen, Steen Dalby; Hochholzer, Willibald; Neumann, Franz-Josef (Thrombosis and Haemostasis, 2013)
Dual antiplatelet therapy with aspirin and clopidogrel in patients undergoing percutaneous coronary intervention (PCI) and in patients with acute coronary syndromes (ACS) has substantially decreased the rate of cardiovascular events. Within the past decade, the variability in pharmacodynamic response as well as the moderate antiplatelet efficacy of clopidogrel has raised major concerns, since high on-clopidogrel platelet reactivity has consistently been associated with increased risk for ischaemic events in PCI patients. The variability in response could be linked to genetic polymorphisms impacting on activity of cytochrome P450 enzymes as well as clinical and demographic variables, but, taken together, factors identified so far can explain only up to approximately 12% of this variability in adenosine diphosphate-induced platelet aggregation on clopidogrel. Regulatory agencies as well as major cardiac societies suggest the use of other anti-platelet medications or alternative dosing strategies for clopidogrel in patients with reduced effectiveness of clopidogrel. This review will focus on the current status of alternate strategies for more sufficient suppression of high platelet reactivity.
Keywords: P2Y12 antagonists; platelet function; clopidogrel